SENP3 Promotes an Mff-Primed Bcl-xL-Drp1 Interaction Involved in Cell Death Following Ischemia - Guo, Chun; Hildick, Keri L.; Jiang, Juwei; Zhao, Alice; Guo, Wenbin; Henley, Jeremy M.; Wilkinson, Kevin A. (Frontiers in Cell and Developmental Biology, 2021)
Dysregulation of the mitochondrial fission machinery has been linked to cell death following ischemia. The fission event is largely dependent on Dynamin-related protein 1 (Drp1), and is initiated by the recruitment of Drp1 to the mitochondria. During this cellular event Mitochondrial fission factor (Mff) is the major docking protein for Drp1. Drp1 is subject to a protein post-translational modification known as SUMOylation. SUMOylation affects the Drp1-Mff interaction, and Drp1 deSUMOylation, mediated by the SUMO protease SENP3, enhances the Drp1-Mff interaction to promote cell death evoked by reoxygenation following oxygen and glucose deprivation (OGD), an in vitro model for ischemia. Another interacting partner for Drp1 is the Bcl-2 family member Bcl-xL, an important protein in cell death and survival pathways. However, whether SUMOylation/deSUMOyation regulate the Drp1-Bcl-xL interaction, and whether this interaction is involved in ischemic cell death, is unknown. Here we demonstrate that preventing Drp1 SUMOylation by mutating its SUMO target lysines enhances the Drp1-Bcl-xL interaction in vivo and in vitro. Consistent with this, SENP3 promotes the Drp1-Bcl-xL interaction. Mff appears to prime the binding of Drp1 to Bcl-xL at the mitochondria. Interestingly, Mff and Bcl-xL also appear to interact directly, independent of Drp1, through their transmembrane domains. Importantly, SENP3 loss in cells subjected to OGD correlates with reduced Drp1-Bcl-xL interaction, whilst recovery of SENP3 levels in cells subjected to reoxygenation following OGD correlates with increased Drp1-Bcl-xL interaction. Expressing a Bcl-xL mutant with defective binding sites for Drp1 reduces OGD plus reoxygenation-evoked cell death. Thus, SENP3-mediated deSUMOlyation promotes an Mff-primed Drp1-Bcl-xL interaction that contributes to cell death following ischemia.